An innovative light assisted production of acetic acid from CO2 and methanol: a first photocatalytic approach using a reusable cobalt(ii) molecular hybrid at atmospheric pressure - Saini, Sandhya; Samal, Pragnya Paramita; Krishnamurty, Sailaja; Ray, Anjan; Jain, Suman L. (Green Chemistry, 2021)
Acetic acid is an important commodity chemical that is produced either by fermentation processes, or more commonly, through chemical routes such as methanol carbonylation with CO and H-2, acetaldehyde oxidation, or hydrocarbon oxidation. More recently, methanol hydrocarboxylation with CO2 and H-2 under thermal catalytic conditions has attracted interest. The synthesis of acetic acid from easily available CO2 is of great significance yet rarely reported. The present paper describes the first photocatalytic approach for the synthesis of acetic acid from methanol and CO2 under ambient reaction conditions without using molecular hydrogen. The maximum conversion of methanol achieved is 60% with a selectivity of 81% towards acetic acid using an octa-sulfur bound cobalt phthalocyanine (CoPc/S8) photocatalyst without an additional sacrificial electron donor. Product analysis, controlled experiments and DFT calculations suggest the formation of methylene carbene as a reactive intermediate. The developed methodology represents a potentially exciting approach for synthesizing acetic acid utilizing CO2 in a sustainable manner.